Improving force tracking control performance in cooperative robots. (6th July 2017) - Sánchez-Sánchez, Pablo; Arteaga-Pérez, Marco A
In order to obtain the environment's information, cooperative robots could need a lot of sensors. A possible solution to reduce the number of sensors might be the use of control–observer structures. In this article, we have designed a control algorithm by using a modified hybrid computed torque method based on the principle of orthogonalization, but in order to avoid the use of tachometers in the implementation, we are including a velocity observer. The stability proof is developed by using the theory of Lyapunov. Simulation of the proposed control structure compared with a well-known control structure via the performance index analysis is presented. Experimental tests are implemented with the control structure that has the best performance index.